The mythologeme of the mountain spirit in the artistic picture of the world by Ch. T. Aitmatov, K.-E. Kudazhy and S. K. Toka - Pomortseva, Natalia V.; Krasilnikova, Svetlana V.; Tagaev, Mamed Dzh.; Chinloda, Madina S.; Ernisova, Aigerim E. (The New Research of Tuva, 2024)
The article discusses the specific features of artistic reflection in the work of national writers from Kyrgyzstan and Tuva, who use mythological images that originate in folk tales about human encounters with invisible spirits. The novels by Ch. T. Aitmatov and S. K. Toka, as well as K.-E. Kudazhy, are considered to be vivid examples of this. It has been established that the inclusion of mythological elements related to mountain spirits in the novels by Tuvan writers is not only a creative strategy used by the authors to draw on ancient motifs. The ethno-cultural context allows for a “modernization” of the genre of legends and stories about mountain spirits, bringing them closer to readers. Another strategy is presented in Ch. T. Aitmatov’s novel “When the Mountains Fall (The Eternal Bride)”, which depicts the transformation of a folklore mythologeme concerning the mountain spirit. Through the hero’s familiarization with the world of their ancestors, the author reveals the concept of his spiritual development through the acquisition of love, as well as the path he must follow to achieve this goal.